Cobalt catalyzed chemoselective reduction of nitroarenes: hydrosilylation under thermal and photochemical reaction conditions. Issue 30 (28th March 2023) - Panda, Surajit; Nanda, Amareshwar; Behera, Rakesh R.; Ghosh, Rahul; Bagh, Bidraha
Abstract : Cobalt-catalyzed hydrosilylation of nitroarenes is reported for the first time using commercially available Co2 (CO)8 under thermal and photochemical conditions. The scope of this protocol was significantly expanded including drug synthesis. Abstract : Commercially available Co2 (CO)8 was used as an effective catalyst for the hydrosilylation of nitroarenes under both thermal and photochemical conditions. A wide variety of nitroarenes with various functionalities were selectively reduced to aromatic amines. Syntheses of drug molecules expand the potential utility of this protocol. Experimental evidence suggested a radical pathway.